Ecological tourism in the Republic of Kazakhstan: problems and prospects of development - Kenzhina, K.D.; Kulmaganbetova, A.O.; Huszti, Zs. (KSU publ., 2017)
In this scientific article were considered one of the most promising sectors of the economy Republic of Kazakhstan — tourism industry, including the importance and development opportunities of ecological tourism. Accordingly, the history, types and directions of the development of the industry were given definitions and explanations and analysis of the principles and peculiarities of development. Opportunities for the development of ecological tourism are characterized by a radical description of the country's resource potential for this sector. Today, our country pays great attention to the development of tourism as a source of income. The President pointed out that the eco-tourism system, based on its structure and peculiarities, has a great potential for development in the country. But it is well-known that the development of traditional tourism is longterm and expensive. And ecological tourism, in this case, does not require a large amount of money, it not only differs with its complicated infrastructure (hotels, restaurants, roads, communications, etc.), but also now provides priority employment for rural populations. In the process of ecological tourism development, villagers can be mixed with their services such as hotel, kyiz yu, national dishes, horses. To do this, it is necessary to provide basic knowledge of hotel business and prepare road guides for trips to the native land, explaining the benefits to the local population.
Қазақстан Республикасындағы экологиялық туризм: мəселелері мен даму болашағы
Экологический туризм в Республике Казахстан: проблемы и перспективы развития
Keywords: ecological tourism; ecotourism community; economic incentive; economic benefits; infrastructure; investment; basic education; travel; tourism market